Tracheal aspirate RNA sequencing identifies distinct immunological features of COVID-19 ARDS - Aartik Sarma (Nature Portfolio, 2021)
Here, the authors perform transcriptional profiling on tracheal aspirates of adults requiring mechanical ventilation for SARS-CoV2-induced acute respiratory distress syndrome (ARDS) and identify a dysregulated host response predicted to predicted to be potentially modulated by dexamethasone.